Turkish acute lymphoblastic leukemia registry, retrospective phase data - Demirkan, Fatih; Çiftçiler, Rafiye; Sevindik, Ömür Gökmen; Tekgündüz, Emre; Erkurt, Mehmet Ali; Vural, Filiz; Turgut, Burhan; Kaynar, Leylagül; Payzin, Kadriye Bahriye; Doğu, Mehmet Hilmi; Karakuş, Volkan; Altuntaş, Fevzi; et al. (The American Society of Hematology, 2019)
Background and Aim: Significant developments have occurred in clinical management of acute lymphoblastic leukemia (ALL) in adults over recent decades. However, treatment results are still not satisfactory especially in routine practice. The aim of the study was to evaluate the general clinical features, treatment details and outcomes of a large group of patients followed up in multiple centers in Turkey with a diagnosis of ALL.
Keywords: Acute; Lymphoblastic Leukemia Registry; Phase Data